F45 Improvement of physical performance with mediterránean diet in Huntington´s disease. (12th September 2022) - Rivadeneyra-Posadas, Jéssica J; Cubo, Esther; Simón-Vicente, Lucía; Garcia-Bustillo, Álvaro; Saiz-Rodriguez, Miriam; Alcaraz, Raquel; Collazo, Carla; Aguado Garcia, Laura; Castillo, Daniel; Raya-González, Javier; Soto, María; Rodríguez, Alejandro; et al.
Abstract : Rationale: Sarcopenia is associated with frailty, and dependence in older patients. Mediterranean Diet (MeDi) is one of the best models for healthy eating, associated with a better life quality in Huntington´s disease (HD). Targeted physical activity intervention has been identified as beneficial in several health disorders, including sarcopenia. Our aim was to evaluate the relationship between MeDi and physical performance. Method: A cross-sectional, observational study. We included symptomatic and self-ambulatory patients with HD. Sarcopenia and frailty were evaluated using a multifrequency Bioimpedance device SECA mBCA 525 (Hamburg, Germany), and the SARF-C screening questionnaire. Physical performance was evaluated by gait speed test and MeDi adherence using the 14-item MeDi adherence questionnaire. Results: Forty-two HD patients with a mean age 52 ± 12 years, BMI 25.77 ± 4.89; calf circumference 35.46 ± 4.18 cm, grip strength 23.57 ± 10.99 kg, gait speed test 0, 86 ± 0, 17 m/s, and MeDi adherence total score of 8.36 ± 2.29, low MeDi adherence in 18 (43%), and moderate-high MeDi adherence in 24 (57%) participants. Frailty was identified in 12 (29%) cases. In logistic adjusted regression models, MeDi adherence was associated with better physical performance (OR=1.581, 95% CI 1.047-2.388, p = 0.02). Conclusion: A good physical performance prevents progression of sarcopenia and adverse outcomes. According to these preliminary results, MeDi adherence protects against low physical performance and severity sarcopenia in HD. Further longitudinal studies on foods, nutrients, and lifestyle elements that are part of concept of the MeDi are necessary to confirm these results.